2022
DOI: 10.1055/s-0041-1735483
|View full text |Cite
|
Sign up to set email alerts
|

Homoeopathic Simillimum in Treatment of Verruca Plana (Flat Wart): A Case Report

Abstract: Verruca plana are also known as flat warts present as small slightly raised papule often a few millimetres wide in diameter with smooth surface, reddish-brown or flesh-coloured, appearing on the dorsum of hands, shins and face. They are caused by human papillomavirus type 3 and less often type 10, 27 and 41. Conventional treatment methods include applying salicylic acid, liquid nitrogen and podophyllin, 5% fluorouracil ointment, carbon dioxide cryotherapy, interferon injections and loop electrosurgical excisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Other published case studies also reported the usefulness of homoeopathic constitutional medicines in treating different types of warts. 17 18 19 20 However, to substantiate the promising findings, larger studies and the usage of validated outcome assessment tools need to be incorporated for generating more scientific evidences on the subject. This case series is a one-step forward for an enhanced clinical management of cutaneous warts and exploring the feasibility of a rational treatment modality.…”
Section: Discussionmentioning
confidence: 99%
“…Other published case studies also reported the usefulness of homoeopathic constitutional medicines in treating different types of warts. 17 18 19 20 However, to substantiate the promising findings, larger studies and the usage of validated outcome assessment tools need to be incorporated for generating more scientific evidences on the subject. This case series is a one-step forward for an enhanced clinical management of cutaneous warts and exploring the feasibility of a rational treatment modality.…”
Section: Discussionmentioning
confidence: 99%
“…Topical use of acetic acid solutions is one of the treatments for HPV infections, but over-thecounter availability of acetic acid solutions for medical use presents a potential hazard for misuse [1] .Wart treatment is still very challenging in modern dermatology while there is no fully satisfactory course of treatment yet that would guarantee complete recovery, with no relapses [7] . While going through the literature search, we only found a few recent reports published on homeopathic cure of different types of skin warts like Flat wart, Filiform wart etc [8][9][10][11][12][13][14][15][16] .As per another doubleblind randomized placebocontrolled clinical trial conducted by Manchanda RK et al [17] which proves that homoeopathic medicines acts beyond placebo.In this context, the present case report, presenting with palmar warts is managed with individualised homoeopathic medicines, showing the positive role of homoeopathy, in the management of palmar wart.…”
mentioning
confidence: 92%
“…Managing warts remains a significant challenge in contemporary dermatology, as there is currently no fully effective treatment regimen that can guarantee complete recovery without the risk of recurrence [7] . Upon conducting an extensive review of the available literature, we discovered only a limited number of recent reports focusing on the homeopathic treatment of various types of skin warts, including flat warts and filiform warts [8][9][10][11][12][13][14][15][16] . Furthermore, a double-blind, randomized, placebo-controlled clinical trial conducted by Manchanda RK and colleagues [17] has provided evidence demonstrating that homeopathic remedies exhibit therapeutic effects beyond that of a mere placebo.…”
Section: Introductionmentioning
confidence: 99%